2015
DOI: 10.4236/aim.2015.54020
|View full text |Cite
|
Sign up to set email alerts
|

Identification Key for <i>Aspergillus</i> Species Isolated from Maize and Soil of Nandi County, Kenya

Abstract: The aim of this study was to identify Aspergillus species isolated from maize kernels and soils of maize fields of Nandi County using macro and micro morphological characteristics. A cross sectional research design was used in the study and purposive sampling was employed to determine districts of Nandi County and sub locations where sampling was done. This study was part of a larger project whose aim was to survey aflatoxin exposure in the maize value chain. Aspergillus species were isolated from maize and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 14 publications
8
41
0
4
Order By: Relevance
“…Gao et al (2007) showed that Aspergillus flavus was the main pollutant in oilseeds (pistachio, almond, hazelnut), corn, wheat, cereals, and beans, respectively. The results of the studies of Makun et al (2007), Amadi et al (2009) were also consistent with this study (13,14,15,16,17). Because of the saprophyte and widespread toxinogenic fungi such as Aspergillus, rice and cereal products have some relative contamination from the beginning.…”
Section: Results Of Mycotoxins Assaysupporting
confidence: 90%
“…Gao et al (2007) showed that Aspergillus flavus was the main pollutant in oilseeds (pistachio, almond, hazelnut), corn, wheat, cereals, and beans, respectively. The results of the studies of Makun et al (2007), Amadi et al (2009) were also consistent with this study (13,14,15,16,17). Because of the saprophyte and widespread toxinogenic fungi such as Aspergillus, rice and cereal products have some relative contamination from the beginning.…”
Section: Results Of Mycotoxins Assaysupporting
confidence: 90%
“…Aspergillus niger was confirmed by various studies such as Nyongesa et al (2015), Awa et al (2012), Diedhiou et al (2007), Khaskheli et al (2008) among others implicated these fungi species to be the fungi responsible for postharvest diseases of mango associated with fruit rotting during ripening. Mango leaves could also be affected as the dusty charcoal spores of the black mold which could easily be dispersed by air from infected fruits.…”
Section: Discussionmentioning
confidence: 81%
“…and were identified as such. A total of eleven pathogens (Alternaria longipes, Aspergillus fumigatus, Aspergillus niger, Colletotrichum gloesporioides, Fusarium oxysporum, Fusarium mangifera Pestalotiopsis mangiferae, Phoma mangiferae, Phomopsis mangiferae, Pseudofusicoccum spp., and Rhizopus oryzae) were identified and were then described and classified based on conidia and colony morphology as described by Barnett and Hunter (1998), Ellis and Hermanis (2003), Palvic et al (2008), Guo-yin et al (2013), Nyongesa et al (2015), and Gagkaeva (2008). Stock cultures of all the isolates were maintained on PDA slopes in McCartney bottles at 4°C in the dark.…”
Section: Identification Of Foliar Fungal Pathogensmentioning
confidence: 99%
“…These two isolates were revealed typical characteristics of blast pathogen. Besides, pure isolates of A. niger colony aged 7 days was observed as grayish black to black colony with white mycelia at the edge of the fungus colony [17].…”
Section: Isolation Of Microorganismsmentioning
confidence: 99%